Surplus, réserves et provisions en assurance - Dalpé, Jean (Assurances, 1982)
In his article, the author differentiates technical reserves from the capital and surplus of an insurance company. There is indeed a marked difference between the two as the former represents sums set aside by the insurer in order to meet his obligations whereas the latter represents the funds actually belonging to such insurer. Each constitutes a separate source of resources but, particularly in inflationary times, both play a major role in ensuring the solvency of the company.